2007
DOI: 10.3354/meps07078
|View full text |Cite
|
Sign up to set email alerts
|

Seabirds as indicators of marine food supplies: Cairns revisited

Abstract: In his seminal paper about using seabirds as indicators of marine food supplies, Cairns (1987, Biol Oceanogr 5:261-271) predicted that (1) parameters of seabird biology and behavior would vary in curvilinear fashion with changes in food supply, (2) the threshold of prey density over which birds responded would be different for each parameter, and (3) different seabird species would respond differently to variation in food availability depending on foraging behavior and ability to adjust time budgets. We teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(187 citation statements)
references
References 41 publications
(69 reference statements)
6
176
0
Order By: Relevance
“…Some of the day-time foraging behavior will reflect dives for larger prey located at depth for chick provisioning (Ito et al, 2010); however, the majority of the dives conducted during the day were probably dedicated to self-feeding. Piatt et al (2007) estimated that relatively little extra food-energy is required for murre parents to feed their chick: i.e., based on measurements of field metabolic rates (FMR; Gabrielsen, 1994) and assimilation efficiency (87%; Romano et al, 2006), murres need to capture about 512 g of fish (at 5.0 kJ g À 1 wet mass), the equivalent of about 49% of their body mass. Despite this large daily food requirement for self-maintenance, raising a single chick only increases a parent murre food demands by about 8%, which might explain why we did not observe inter-colony differences in chick feeding rates.…”
Section: Foraging Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the day-time foraging behavior will reflect dives for larger prey located at depth for chick provisioning (Ito et al, 2010); however, the majority of the dives conducted during the day were probably dedicated to self-feeding. Piatt et al (2007) estimated that relatively little extra food-energy is required for murre parents to feed their chick: i.e., based on measurements of field metabolic rates (FMR; Gabrielsen, 1994) and assimilation efficiency (87%; Romano et al, 2006), murres need to capture about 512 g of fish (at 5.0 kJ g À 1 wet mass), the equivalent of about 49% of their body mass. Despite this large daily food requirement for self-maintenance, raising a single chick only increases a parent murre food demands by about 8%, which might explain why we did not observe inter-colony differences in chick feeding rates.…”
Section: Foraging Behaviormentioning
confidence: 99%
“…The closely related common murre has been shown to buffer chick-feeding rates and fledging success across a wide range in food availability by reallocating discretionary time spent at the colony to foraging effort Piatt et al, 2007). Reproductive performance is therefore not a good indicator of foraging conditions (Kitaysky et al, 2000), whereas the behavior of adults (colony nest-attendance; Harding et al, 2007), and blood levels of stress hormones have been shown to be directly related to changes in the availability of food resources to chick-rearing murres.…”
mentioning
confidence: 99%
“…This indicates that breeding success is less sensitive to variation in food supply than Cairns' original hypothesis ( Figure 1A). The study by Cury et al (2011) re-analyzed data from populations examined by other studies included in our review (e.g., Oro and Furness, 2002;Crawford et al, 2006;Piatt et al, 2007a). Although they found only asymptotic relationships (and one non-significant relationship) across species (Cury et al, 2011), the original studies reported the full range of functional responses to changes in fish stocks (no relationship, linear, asymptotic, step), with asymptotic relationships being the most common.…”
Section: Breeding Successmentioning
confidence: 99%
“…The one study that considered foraging trip duration reported a negative exponential relationship with fish stocks, where trip duration varied across the entire range of fish stocks. Three cases considered colony attendance, and a different relationship was reported for each species; only one species (common murre, Uria aalge) showed a strong relationship with fish stocks, where attendance during chick rearing varied in the lower 60% of observed fish stocks (Harding et al, 2007a,b;Piatt et al, 2007a). Furthermore, the relationship between colony attendance and fish stocks was driven by differences between colonies monitored by sight or by video camera (Harding et al, 2007a,b;Piatt et al, 2007a), and it is possible that visual observations missed some attendance periods.…”
Section: Chick Growth Rate and Massmentioning
confidence: 99%
“…Seabird population and community dynamics respond to local to large spatio-temporal scales in marine ecosystems (e.g., fronts to ocean basins and days to decades), such that their distribution and abundance at sea can serve as indicators of marine ecosystem variability (Veit et al 1997, Hyrenbach and Veit 2003, Ainley et al 2009, Piatt et al 2007, Sydeman et al 2009, 2015. Many seabird species exhibit long-distance migrations among disparate marine ecosystems and hemispheres to feed on seasonally abundant forage species (Veit et al 1996, Shaffer et al 2006, and therefore may affect marine food webs regionally and globally.…”
Section: Introductionmentioning
confidence: 99%